Diagnosis of social phobia in adults. Reliable methods of clinical evaluation and diagnostic tools - Małgorzata Reiter (Rozprawy Społeczne)
Abstract The methods of diagnosing Social Phobia currently used in Poland can be divided into two groups: structured or unstructured psychological/psychiatric interviews and questionnaires/scales/inventories used to assess symptoms. This article presents reliable methods of diagnosing Social Phobia, taking into account their specific diagnostic properties. For the purposes of this article, the term Social Phobia is used interchangeably with the terms Social Anxiety and Social Anxiety Disorder, as all terms relate to the topic being discussed and appear interchangeably in diagnostic classifications, scientific publications, and the discussed diagnostic tools.